2023
DOI: 10.1002/ps.7446
|View full text |Cite
|
Sign up to set email alerts
|

Fus3/Kss1‐MAP kinase and Ste12‐like control distinct biocontrol‐traits besides regulation of insect cuticle penetration via phosphorylation cascade in a filamentous fungal pathogen

Abstract: BACKGROUND: Homolog of the yeast Fus3/Kss1 mitogen-activated protein kinase (MAPK) pathway and its target transcription factor, Ste12-like, are involved in penetration of host cuticle/pathogenicity in many ascomycete pathogens. However, details of their interaction during fungal infection, as well as their controlled other virulence-associated traits, are unclear.RESULTS: Ste12-like (BbSte12) and Fus3/Kss1 MAPK homolog (Bbmpk1) interacted in nucleus, and phosphorylation of BbSte12 by Bbmpk1 was essential for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(171 reference statements)
0
1
0
Order By: Relevance
“…Despite this increase, however, one consequence of Msg5 upregulation in the ΔBbOsrR2 strain may be dampening of the Fus3/Kss1 MAP kinase signaling which would result in decreased virulence and reduced conidial production, phenotypes seen for the ΔBbOsrR2 strain. Disruption of the Fus3/Kss1 MAP kinase gene, Bbmpk1, in B. bassiana also results in decreased virulence, but unlike the ΔBbOsrR2 mutant, increased growth is also seen [54,55]. Expression of Cdc28, involved in cell cycle progression, acting as downstream factor of the Fus3/Kss1 MAP and Hog1 MAP kinase pathways [47,56,57], was also significantly upregulated in the ΔBbOsrR2 strain, potentially helping account for the conidiation and germination defects seen.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this increase, however, one consequence of Msg5 upregulation in the ΔBbOsrR2 strain may be dampening of the Fus3/Kss1 MAP kinase signaling which would result in decreased virulence and reduced conidial production, phenotypes seen for the ΔBbOsrR2 strain. Disruption of the Fus3/Kss1 MAP kinase gene, Bbmpk1, in B. bassiana also results in decreased virulence, but unlike the ΔBbOsrR2 mutant, increased growth is also seen [54,55]. Expression of Cdc28, involved in cell cycle progression, acting as downstream factor of the Fus3/Kss1 MAP and Hog1 MAP kinase pathways [47,56,57], was also significantly upregulated in the ΔBbOsrR2 strain, potentially helping account for the conidiation and germination defects seen.…”
Section: Discussionmentioning
confidence: 99%
“…The Fus3-MAP kinase-mediated cascades have been shown to control the morphological transition of fungal pathogens, such as the infection structure (appressorium) formation or function, development of infective hyphae, dimorphism, and sporulation, despite the difference in fungal species ( 10 , 40 ). The pathway also mediates adaptation to oxidative stress derived from insect immune response-generated reactive oxygen species in some fungal species ( 41 ). The Hog1-MAP kinase pathway controls osmotic, oxidative, and thermal stress responses, as well as sporulation, viability, and fungal virulence ( 33 ), and has been implicated in mediating adaptation to low oxygen niches in fungal-infected insect hemocoel ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…62 Msn2 controls cell wall integrity-included multi-stress responses, growth, conidiation and virulence, and negatively regulates protease, lipase and oosporein production. 63,64 Ste12 regulates growth, conidiation and cuticle penetration, 65 and a C repressor CreA plays a much broader role in fungal development, cell homeostasis, cuticle penetration and virulence in the fungal pathogen. 44 These results suggested that those chitinase genes and BbHex1 might be commonly or cooperatively regulated by these transcription factors, contributing cell wall (chitin) biosynthesis, cuticle penetration and virulence, as well as evasion of immune response.…”
Section: Discussionmentioning
confidence: 99%